Two new remarkable and endangered catfish species of the genus Cambeva (Siluriformes, Trichomycteridae) from southern Brazil - Costa, Wilson J.E.M.; Feltrin, Caio R.M.; Katz, Axel M. (European Journal of Taxonomy, 2022)
During a field inventory directed at trichomycterine habitats, two new species of the genus Cambeva, C. alphabelardense sp. nov. and C. betabelardense sp. nov., were found in the Rio Chapecó drainage, an area under high environmental decline due to intensive soya monoculture. These species share a peculiar head morphology and some unique osteological features, besides having a size that is smaller than in any other congener, being herein considered to be more closely related to each other than to other taxa. They differ from each other by several characters, including head shape, fin morphology, number of jaw teeth and opercular odontodes, and mesethmoid and metapterygoid shape. Furthermore, they were found in the same area, but in distinct biotopes, with one species found buried in the remnants of tree ferns and other plants on the stream bottom, restricted to a small residual fragment of the original forest, and the other species inhabiting a stream with gravel and small stones on the bottom. Field studies indicate that these species are threatened with extinction. Robust phylogenetic studies are still necessary to test relationship hypotheses involving the new taxa here described.